The journey of islet cell transplantation and future development. Issue 2 (4th March 2018) - Gamble, Anissa; Pepper, Andrew R.; Bruni, Antonio; Shapiro, A. M. James
ABSTRACT: Intraportal islet transplantation has proven to be efficacious in preventing severe hypoglycemia and restoring insulin independence in selected patients with type 1 diabetes. Multiple islet infusions are often required to achieve and maintain insulin independence. Many challenges remain in clinical islet transplantation, including substantial islet cell loss early and late after islet infusion. Contributions to graft loss include the instant blood-mediated inflammatory reaction, potent host auto- and alloimmune responses, and beta cell toxicity from immunosuppressive agents. Protective strategies are being tested to circumvent several of these events including exploration of alternative transplantation sites, stem cell-derived insulin producing cell therapies, co-transplantation with mesenchymal stem cells or exploration of novel immune protective agents. Herein, we provide a brief introduction and history of islet cell transplantation, limitations associated with this procedure and methods to alleviate islet cell loss as a means to improve engraftment outcomes.